Bayesian Optimized Pretrained CNNs for Mango Leaf Disease Classification: A Comparative Study - Rahayu, Sri; Romdoni, Sayyid Faruk (Jurnal Teknik Informatika (Jutif), 2025)
Mango leaf diseases pose a major threat to crop productivity, causing significant economic losses for farmers. Accurate and early detection is essential, yet manual diagnosis remains subjective and inefficient. This study aims to evaluate and compare the performance of five pretrained Convolutional Neural Network (CNN) architectures—DenseNet121, ResNet50V2, MobileNetV3 Small, MobileNetV3 Large, and InceptionV3—by systematically optimizing their hyperparameters to identify the most effective model for mango leaf disease classification. The public MangoLeafBD dataset, containing 4,000 images from eight balanced classes, was used. Bayesian Optimization was applied to fine-tune each model, and their performances were assessed before and after optimization. Results show that optimization substantially improved all models, with MobileNetV3 Large achieving the highest accuracy of 100% on the test set, followed by DenseNet121 (99.75%), ResNet50V2 (99.63%), MobileNetV3 Small (99.50%), and InceptionV3 (98.50%). The findings highlight that a well-tuned lightweight model can outperform more complex architectures, offering a practical and efficient solution for developing mobile-based diagnostic tools to support precision agriculture in resource-constrained settings.